CECILIA: Ultradeep Rest-optical Spectra of Faint Galaxies at Cosmic Noon - Menelaos Raptis; Ryan F. Trainor; Allison L. Strom; Gwen C. Rudie; Noah S. J. Rogers; Charles C. Steidel; Michael V. Maseda; Caroline von Raesfeld; Nathalie A. Korhonen Cuestas (The Astrophysical Journal Letters)
Intrinsically faint galaxies at z ∼ 2–3 offer critical insights into early galaxy formation, tracing low-metallicity, low-mass systems during cosmic noon and serving as analogs to reionization-era galaxies. We present ultradeep JWST/NIRSpec spectroscopy of nine low-luminosity galaxies (−17 ≲ M _UV ≲ −20, M _⋆ ≲ 10 ^9 M _⊙ ) at z ∼ 2.5 from the CECILIA program, with ∼29.5 hr in G235M/F170LP and 1 hr in G395M/F290LP. Our sample includes four Ly α emitters, three rest-UV color-selected galaxies, and two serendipitous detections, providing the most sensitive rest-optical spectra of individual faint galaxies at this epoch to date. Balmer-line measurements reveal low star formation rates (SFRs; 0.63 < SFR/( M _⊙ yr ^−1 ) < 5.43) and a broad range of dust reddening (0 < E ( B − V ) < 1), with SFRs systematically below those of continuum-selected galaxies. Electron densities are low ( n _e ≲ 200 cm ^−3 ), and emission-line diagnostics indicate low [N II ]/H α and high [O III ]/H β , suggesting metallicities of $12+{log}\,({\rm{O}}/{\rm{H}})\lesssim 8.0$ . We also present the first O1-BPT constraints in such faint high-redshift galaxies. Notably, two galaxies show low [O III ]/H β despite high Ly α EWs and very low [N II ]/H α , consistent with the predicted turnover in this ratio at very low metallicities, highlighting the need for complementary diagnostics (e.g., N2, O32) to identify metal-poor systems. Direct T _e -based abundances and expanded samples are needed to further trace metallicity and ionization trends in low-mass galaxies.